Advancing Sustainable Development Goals through Islamic Education: A Mixed-Methods Study among Scientific Disciplines at the University of Zawia - Lubnah Abdullaha; Najah Baroud; Fatima Alsaeh; Amaal kasheem; Khuloud Alouzi; Najimudin Shalghoum; Mahmoud Abdullah; Husna Nashihin (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the role of the Islamic Education as a required course in developing awareness, understanding, and behavioral intentions related to Sustainable Development among students in scientific disciplines at the University of Zawia, Libya. Although sustainability has become as a national priority in Libya and North Africa in general, higher education institutions often struggle to embed sustainability principles within curricula, especially in non-specialized general courses. Using a mixed-methods design, the study collected quantitative data from 250 students in mathematics, biology, chemistry, computer science, and physics, supported by qualitative interviews with ten lecturers teaching the Islamic Education course. Descriptive analysis of the questionnaire responses showed moderate to high levels of sustainability awareness, with the course contributing significantly to students’ ethical understanding of environmental and social responsibilities rooted in Islamic concepts. Students also evaluated the course's teaching methods positively, although they expressed their need for more applied, modern and interdisciplinary approaches. The findings further demonstrated that the course positively influenced students’ attitudes and behavioral intentions toward adopting sustainable practices in their personal and future professional careers. Thematic analysis of lecturer interviews supported these results, highlighting pedagogical strategies, challenges, and opportunities for strengthening sustainability integration. The study concludes that the Islamic Education course serves as a valuable ethical and intellectual framework for promoting sustainability among scientific majors in Libyan higher education. Recommendations include curriculum enhancement, interdisciplinary collaboration, and the development of institutional regulations to support sustainability initiatives.